Dementia (Slide Presentation) - Shalihin, Mohd Shaiful Ehsan; Wan Mamat, Wan Hasliza; Mohamad Zahir, Mohd Zulkifli; Mohammad Aidid, Edre (2021)
This slide presentation consists of the presentation regarding Dementia included in the program of Early detection of Mild Cognitive Impairment and Prevention of Dementia in Rumah Ehsan, Dungun, Terengganu.